An Analysis of Language Style in Political Debate of Indonesian Presidential Candidate of 2024 - Nentriana Hutabarat; Sondang Manik; Jubilezer Sihite (Universitas Islam Negeri Palopo, 2025)
This research aims to identify various types of language styles and try to find the most dominant use of language styles in the political debates of the 2024 Indonesian presidential candidates using a sociolinguistic approach. This study uses a qualitative method. To obtain data, the author used a note-taking technique, namely taking notes. Because the data was in the form of words, it was analyzed by identifying, analyzing, and categorizing the data and noting the frequency of the most dominant types of language styles. Researchers also used Martin Joos's theory of language style types; five different language styles were studied. Frozen style is one of them, as are formal style, consultation style, casual style, and intimate style. The results of the research show that the types of language styles in political debates have a frozen style of 1 data, a formal style of 3 data, a consultative style of 35 data, then a casual style of 12 data, and finally the intimate style has 0 data. Based on the analysis, the author found that there are four language styles: frozen, formal, consultative, and relaxed. Then, the consultative style is the most widely used style, with 35 data points out of a total of 51 data points.